Inkjet Printing of Aqueous Silver Inks on Water-Soluble Fabrics for Transient Electronics Applications - Onses, Zehra Gozutok; Kiremitler, N. Burak; Ozbasaran, Aleyna; Huang, Xian; Onses, Mustafa Serdar; Usta, Hakan; Gozutok Onses, Zehra (Amer Chemical Soc, 2024)
There is an urgent need to develop practical routes for manufacturing transient electronic devices to tackle the emerging issue of electronic waste and enable next-generation devices. This study reports additive patterning of conductive layers on industrially available water-soluble nonwoven fabrics composed of poly(vinyl alcohol) (PVA). Aqueous inks composed of reactive silver precursors can be practically patterned over water-soluble fabrics by inkjet printing. The efficient deposition of materials with droplet volumes on the order of picoliters ensures the generation of conductive patterns on a water-soluble fabric using a solution-processable fabrication with aqueous inks. The fabrication of conductive electrodes and transience behavior are studied on PVA fabrics with two different degrees of hydrolysis, providing tunability in the temperature-dependent degradation of the substrate. The application of the printed conductive pads is demonstrated in resistive heaters. The temperature of the fabric can exceed 100 degrees C in less than 15 s at a safe voltage of 3 V. The heater exhibits stable operation under cyclic heating and cooling. The presented approach presents key opportunities in additive patterning of aqueous solutions and colloidal dispersions over water-soluble substrates for transient device applications.
Onses, Mustafa Serdar/0000-0001-6898-7700; Huang, Xian/0000-0002-8788-9185;
Keywords: Transient Electronics; Inkjet Printing; Silver; Poly(Vinyl Alcohol); Electronic Textiles; Resistiveheaters; Resistive Heaters